The performance-level model of hospital decontamination preparedness. - Phelps, Scot; Doering, Garrett (American journal of disaster medicine, 2008)
OBJECTIVE: Describe a multilevel model of decontamination capacity for hospitals., DESIGN: Descriptive model., SETTING: Acute care hospitals with decontamination responsibilities., PATIENTS, PARTICIPANTS: None., INTERVENTIONS: None., MAIN OUTCOME MEASURE(S): None., RESULTS: This multilevel model of defining decontamination capacity would allow more realistic assessment of current capacity, allow for fluctuating service levels depending on time of day, incorporate realistic ramp-up and ramp-down of decontamination services, allow for a defined fall-back decontamination model should decontamination processes fail, allow hospitals to define long-term decontamination service level goals, and allow better understanding of when and why to focus on low-risk/low-resource patients rather than high-risk/high-resource patients., CONCLUSIONS: This multiple-level model would allow for more realistic and effective hospital-based decontamination service models and should become part of the national decontamination paradigm.
1 citations (Crossref) [2023-10-31] Place: United States Phelps, Scot. Department of Public Health, School of Health and Human Services, Southern Connecticut State University, New Haven, USA.
Keywords: *Decontamination/st [Standards]; *Disaster Planning/st [Standards]; *Emergency Service; Hospital/og [Organization & Administration]; *Hospital Administration/st [Standards]; *Models; Organizational; Decontamination; Disaster Planning; Emergency Service; Hospital; Hospital Administration; Hospitals; Hospitals/st [Standards]; Humans; MLCS; MLOWN; Models; Organizational; Terrorism; article; dept.hms; disaster planning; emergency health service; hospital; hospital management; human; nonbiological model; organization and management; standard; terrorism; waste management